PENGARUH SIKAP INDEPENDENSI, PROFESIONALISME, PENGALAMAN KERJA, KOMPETENSI DAN KUALITAS KINERJA INTERNAL AUDITOR TERHADAP EFEKTIVITAS STRUKTUR PENGENDALIAN INTERN (Studi Kasus Pada PT Bank BRI PerseroTbk Kab. Purworejo) - Supriono Supriono (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2017)
Bank Rakyat Indonesia (BRI) is one of the largest goverment owned bank in Indonesia. At BRI are resident auditor unit as an internal auditor. Internal auditor should heve an attitude of independence, professionalism, work experience, competence, and quality performance that is able to influence the effectiveness of the internal control structure in BRI. This study uses primary data through questionnaires conducted on 12 unit of BRI and 1 branch in Kutoarjo. The number of espondents as many 36 respondents. The sampling is done by using puposive sampling. The data analysis technique used is the hypothesis testing multiple liniar regression and coorelation. The result showed that (1) the attitude of the independence of the internal auditor has a significance level of 0,584 greater than 0,05, whice mean a positive however not significant effect on the effectiveness of the internal control structure. (2) the professionalism of internal auditors have a significance level of 0,119 greater than 0.05 whice means a positive however not significant effect on the effectiveness of internal control structure. (3) the internal auditor`s work experience has a significance level of 0,446 greater than 0,05 whice means a positeive however not significant effect on effectiveness of the internal control structure. (4) the competence of internal auditors have a level of significance 0,000 less than 0,05, whice means positive and sifnificant impact on the effectiveness of the internal control structure. (5) the quality of work of iternal auditors have a significance level of 0,039 less than 0,05 were positive and significant impact on the effectivencess of internal control structure. Keywords : attitude independence, professionalism, work experience, competence, quality, performance, effectiveness of internal control structure BRI